Epstein–Barr virus‐driven B Cell Proliferation with CD4+ T Cell Expansion: A Lymphomatoid Granulomatosis‐like Disease Related to Hyperinterleukin‐10 Secretion of Remarkably Favourable Outcome with Rituximab. (December 2015) - Cervera, P.; Guihot, A.; Gorochov, G.; Lassoued, K.; Coppo, P.
Abstract Granulomatous lymphomatosis is an Epstein–Barr virus (EBV)‐driven B cell proliferation associated with an exuberant CD4+ T cell reaction with usually histopathological pictures of angiocentrism. So far, the characteristics of CD4+ T cells in granulomatous lymphomatosis and the mechanism leading to their expansion remain poorly explored. We report a 56‐year‐old female with a past history of cold agglutinin disease, which was successfully treated with 4 weekly infusions of rituximab. She presented one year later with features of granulomatous lymphomatosis that resulted in severe lung and bone marrow infiltration. We provide evidence that CD4+ T cell expansion was oligoclonal, involved anergic cells and did not result from an EBV‐driven stimulation. Rather, it resulted possibly from a high production of interleukin‐10 by immunoblastic EBV‐positive B cells. The outcome was remarkably favourable with rituximab and steroids. Our results suggest that an EBV‐driven B cell proliferation should be investigated in patients presenting with a CD4+ T cells alveolitis or other systemic manifestations resulting from a CD4+ T cell expansion. These features should prompt to introduce an immunosuppressive therapy including steroids and rituximab. Our results deserve further investigations to confirm our pathophysiological hypotheses in CD4+ T cell expansions associated with EBV‐driven B cell proliferations and to assess whether granulomatous lymphomatosis could result from comparable mechanisms.